High-moisture corn grain silage inoculated with Propionibacterium acidipropionici and Lactobacillus plantarum in different storage times (Research, Society and Development, 2021)
The aim of this study was to evaluate the chemical composition, growth of microorganisms, and the aerobic stability of high-moisture corn grain silage inoculated with Lactobacillus plantarum + Propionibacterium acidipropionici. The experimental design was completely randomized in a 2 x 5 factorial arrangement with four replications (50 experimental units)  and the treatments were: use or not of microbial inoculant (2 x 105 colony forming unit (CFU) g-1 Lactobacillus plantarum + Propionibacterium acidipropionici) and the storage length for 0, 1, 3, 7, and 14 d. Aerobic stability of silage was evaluated at 28 and 56 d of storage length. The lactic acid bacteria population was influenced by storage length and the greatest values were estimated at 8 d of storage length. Regardless of inoculant application, no enterobacteria were present from 3 d post-ensiling. With respect to mold growth, an interaction between inoculant and storage length was observed wherein molds were most abundant after 3 d of storage in silage that received inoculant. However, at 14 d of storage the use of bacterial inoculant reduced the occurrence of molds. pH values obtained after 3 d of ensiling were less than 4.0 for all the treatments. The high-moisture corn grain silage possessed good fermentative quality. Further, adequate pH values were achieved from the third day of ensilage and were not influenced by the presence of bacterial inoculant.